(untitled) (Tigbauan, Iloilo, Philippines, 1988)
The report provides a presentation of perspectives in aquaculture development in Southeast Asia and Japan
Keywords: Nuôi trồng thủy sản,Aquaculture,Aquaculture; Đông Nam Á,Southeast Asia,Japan